Variabilidade dos estoques de carbono orgânico, nitrogênio total e do efluxo de CO2 em neossolos sob floresta de Caatinga - Souza, Renato Francisco da Silva (2021)
Quantifying soil organic carbon (COS), soil total nitrogen (NTS) stocks and soil CO2 efflux in different biomes around the world is critical to understanding global climate change. However, accurate quantification is highly challenging due to high variability, especially in forest ecosystems. Therefore, this research aimed to evaluate the variability of soil organic carbon (SOC) stocks, total nitrogen (TSN) and CO2 efflux stocks in Leptosol under Caatinga forest. The research was carried out at the Experimental Station Professor Ignácio Salcedo, at the Instituto Nacional do Semiárido, in the municipality of Campina Grande, Paraíba, Brazil. A total of 363 soil samples were collected in 10 cm layers thick, up to a depth of 50 cm, following a cyclic sampling model in a 350 m transect. The stocks of SOC and TSN in 0-50 cm depth ranged between 20.23 and 94.78 Mg ha-1 and 1.48 and 8.37 Mg ha-1, respectively. The stocks of SOC and TSN had a moderate degree of spatial dependence at 0-10 and 10-20 cm layers and strong in the underlying layers. The spatial autocorrelation distance of the SOC and TSN stocks ranged, respectively, from 49.63 to 72.32 m and from 48.98 to 70.23 m. The rock fragments contents, clay, Pextractable, SOC and TSN influence the COS and NTS stocks, and this influence varies with the soil layer. The stocks of SOC and TSN show moderate variability in each soil layer was classified as moderate, based on the coefficients of variation. The spatial autocorrelation distance for both stocks is dependent on the depth of the soil and therefore should be considered when optimizing sampling. The variability of soil CO2 efflux was assessed through measurements in 42 points, randomly distributed over an area of approximately 0.72 ha. The soil CO2 efflux varied of 0.47 to 4.14 µmol of CO2 m-2 s-1 in a dry and wet season, respectively. The volumetric soil water content explained about 93% of the temporal variability of soil CO2 efflux and soil temperature explained 52%. The autocorrelation spatial distance of soil CO2 efflux oscillated of 5.7 to 64.3 m and were smaller during the dry season. The research revealed that the temporal variability of soil CO2 efflux is mainly controlled by the volumetric soil water content. To quantify the efflux of CO2 from the soil, a distance between points greater than 64.3 m must be adopted, for the measurements to be considered statistically independent.